SINTESIS DAN KARAKTERISASI SILIKA GEL DARI LIMBAH KACA SERTA APLIKASINYA PADA KROMATOGRAFI KOLOM - Verry Andre Fabiani; Nelly Wahyuni; Ridho Brilliantoro; Mellisa Nurul Safitri (Indonesian Journal of Pure and Applied Chemistry, 2018)
Silica gel synthesis from glass waste have been carried out with activation and purification method by using hydrochloride acid. Hydrochloride acid were varied 8 N, 10 N, and 12 N to observe optimum concentration in purification of silica gel and component separation in chromatography column. Gravimetric analysis result showed 12 N hydrochloride acid produce ~100 % silica. XRD and FTIR analysis revealed that synthetic gel silica was amorphous where its IR absorption bands were at 3426 cm-1, 1620 cm-1, 1080 cm-1, 772 cm-1 and 478 cm-1. The absorption bands agreed to standard gel silica and spectrum. The most effective HCl in gel silica synthesis was 12 N, caused by its ability to separate color component in a column. The synthetic silica that can be applied as stationary phase in column chromatography.